Efficacy and Safety of a Novel Thrombectomy Device in Patients With Acute Ischemic Stroke: A Randomized Controlled Trial - Zhang, Yongxin; Hua, Weilong; Li, Zifu; Peng, Ya; Han, Zhian; Li, Tong; Yin, Congguo; Wang, Shoucun; Nan, Guangxian; Zhao, Zhenwei; Yang, Hua; Zhou, Bin; et al. (Frontiers in Neurology, 2021)
Abstract Purpose: The Tonbridge stent is a novel retriever with several design improvements which aim to achieve promising flow reperfusion in the treatment of acute ischemic stroke (AIS). We conducted a randomized, controlled, multi-center, non-inferiority trial to compare the safety and efficacy of the Tonbridge stent with the Solitaire FR. Methods: AIS patients aged 18-85 years with large-vessel occlusion in anterior circulation who could undergo puncture within 6 hours of symptom onset were included. Randomization was performed on a 1:1 ratio to thrombectomy with either the Tonbridge stent or the Solitaire FR. The primary efficacy endpoint was successful reperfusion using a modified thrombolysis in cerebral infarction score (mTICI) of 2b/3. Safety outcomes were symptomatic intracranial hemorrhage (sICH) within 24±6 hours and all-cause mortality within 90 days. Secondary endpoints included time from groin puncture to reperfusion, National Institutes of Health Stroke Scale (NIHSS) score at 24 hours and at 7 days, and a modified Rankin Scale (mRS) score of 0-2 at 90 days. Results A total of 220 patients were enrolled; 104 patients underwent thrombectomy with the Tonbridge stent and 104 were treated with the Solitaire FR. In all test group patients, the Tonbridge was used as a single retriever without rescuing by other thrombectomy devices. Angioplasty with balloon and/or stent was performed in 26 patients in the Tonbridge group, and 16 patients in the Solitaire group (P=0.084). Before angioplasty, 86.5% of those in the Tonbridge group and 81.7% of those in the Solitaire group reached successful reperfusion (P=0.343). Finally, more patients in the Tonbridge group achieved successful reperfusion (92.3% vs. 84.6%, P<0.0001). There were no significant differences on sICH within 24±6 hours between the two groups. All-cause mortality within 90 days was 13.5% in the Tonbridge group and 16.3% in the Solitaire group (P=0.559). We noted no significant differences between groups on the NIHSS at either 24 hours or 7 days, and the mRS of 0-2 at 90 days. Conclusion The trial results indicated that the Tonbridge stent was non-inferior to the Solitaire FR within 6 hours of symptom onset in cases of large vessel occlusion stroke. (ClinicalTrials.gov number, NCT03210623)